Accelerometer-based and self-reported physical activity of children and adolescents from a seasonal perspective - Eckelt, Melanie; Hutmacher, Djenna; Steffgen, Georges; Bund, Andreas (Frontiers in Sports and Active Living, 2024)
Background: Many children and adolescents in Europe are insufficiently physical active, which makes the promotion of children´s physical activity a critical health promotion target. However, there are some environmental factors, such as the amount of daylight, weather conditions, temperatures and precipitation levels, which might influence physical activity behavior. The purpose of this study was to assess accelerometer-based and self-reported daily physical activity of children and adolescents in Luxembourg during autumn/winter as well as during spring/summer and to examine if there is a seasonal influence on the physical activity behavior. Methods: At two measurements, one in autumn/winter and one in spring/summer, physical activity of N = 137 (59.12% females; M = 12.37 years) participating children and adolescents aged 10-18 years was objectively measured via accelerometer (ActiGraph) and subjectively assessed using among others one item of the MoMo physical activity questionnaire. Results: A repeated measures ANOVA revealed a significant seasonal effect for moderate to vigorous physical activity per day (F(1.000, 135.000) = 7.69, p < .05, partial η² = .054). More minutes of moderate to vigorous physical activity per day were accrued in spring/summer than in autumn/winter. Mean difference scores between accelerometer-based and self-reported physical activity at T1 and T2 correlated significantly (r = .31, p < .001). Conclusions: According to these results, children and adolescents are less physically active in autumn/winter than in spring/summer. However, the discrepancy between accelerometer-based and self-reported physical activity remains stable over the two measurements. Therefore, schools, sports clubs and communities should offer special physical activity programs for the colder season.